2004
DOI: 10.1002/jemt.20020
|View full text |Cite
|
Sign up to set email alerts
|

Methods for determining the composition of nasal fluid by X‐ray microanalysis

Abstract: The nasal fluid is an easily accessible form of airway surface liquid. The objective of this study was to find a technically easy and reproducible method for sampling and analysis of this fluid. In a pilot study, several methods to carry out X-ray microanalysis of sub-microliter droplets were compared. Acceptable results were obtained with several of these methods (pipeting on filter paper or analysis of frozen-hydrated droplets at low temperature). Nasal fluid was collected from the inferior turbinate with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…In the frozen-hydrated trachea, the entire ASL is sampled, with probably a predominance of the upper mucous layer. Airway mucus has a composition that is different from that of the watery fraction (20). Apart from mucus macromolecules contributing S, this layer also contains cell debris that would contribute elements such as P and K. Leakage from dead cells could partially explain the relatively high K concentration in the watery fraction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the frozen-hydrated trachea, the entire ASL is sampled, with probably a predominance of the upper mucous layer. Airway mucus has a composition that is different from that of the watery fraction (20). Apart from mucus macromolecules contributing S, this layer also contains cell debris that would contribute elements such as P and K. Leakage from dead cells could partially explain the relatively high K concentration in the watery fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The needle was connected to a syringe previously filled with air, and the beads were sprayed evenly over the tracheal surface by pressure on the syringe. Earlier experiments have shown that saturation of the beads with a salt solution is obtained after 5 min (20). After absorption of the ASL, the beads were recovered by being flushed with hydrophobic volatile silicone oil (Dow Corning 200/1cS; BDH, Poole, UK) and collected in a watch glass (12).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sephadex is the trade name for a cross-linked dextran gel with ion-exchange capacity, and these beads saturate with salt solution within about 5 min [19]. The beads may be sprayed on to a sample via a syringe, or mounted on a filter paper (see Section 9) and it is important that the beads are well spread and do not stick together.…”
Section: Collection Of Tracheal Fluid On Ion-exchange Beadsmentioning
confidence: 99%